Cobertura, estructura vegetal y almacenamiento de carbono del manglar de Morales, Puntarenas, Costa Rica - Cambronero Bolaños, Rebeca (2025)
Introduction: Mangrove forests provide diverse ecosystem services. However, mangroves are one of the most impacted tropical ecosystems, mainly due to land use change, as has occurred in the Gulf of Nicoya in Costa Rica. Objective: Analyze mangrove spatial cover over time, and forest structure, and the carbon storage of the mangrove forest of Morales, to generate a current base line of the state of the mangrove forest. Methods: The study was carried out in the mangrove forest of Morales, Puntarenas, Costa Rica. Total mangrove forest area was calculated from aerial photographs between 1944 and 2020. In 2021, 5 × 5 m plots were sampled in the field. In each plot, trees were counted, they were identified to the lowest possible taxon, their height were measured, and their circumference to calculate their diameter, and soil samples of 4.5 cm depth and interstitial water were collected. The complexity index (CI) of the mangrove stand and the importance value (IV) were calculated for each mangrove genus. Organic carbon content (Corg) was calculated from allometric equations for trees and with loss on ignition for soil. Results: The mangrove forest area decreased by 24 ha between 1944 and 2020, mainly because of the development of shrimp and salt ponds. The forest CI in 2021 was 18.3 and the genus of greatest importance was Rhizophora. The mangrove forest stores 48 Mg Corg/ha in living vegetation and 11 Mg Corg/ha in the soil up to 4.5 cm depth. Conclusions: The mangrove forest structure and the carbon storage, in general, are similar to other mangrove stands in the Gulf of Nicoya. Considering only the carbon in the above ground living vegetation, the loss of 24 ha is equivalent to 4 224 Mg CO2 released. The feasibility of carrying out ecological restoration of the lost areas could be analyzed.